Method for conversion between the two coded character sets of BS 4730 (ISO 646) and BS 6692:Part 2 (ISO 6937-2) and the CCITT international telegraph alphabet No. 2 (ITA 2). (31st August 1989) - British Standards Institution,
No abstract available